2001
DOI: 10.1073/pnas.121013398
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of the SarR protein from Staphylococcus aureus

Abstract: The expression of virulence determinants in Staphylococcus aureus is controlled by global regulatory loci (e.g., sarA and agr). The sar (Staphylococcus accessory regulator) locus is composed of three overlapping transcripts (sarA P1, P3, and P2, transcripts initiated from the P1, P3, and P2 promoters, respectively), all encoding the 124-aa SarA protein. The level of SarA, the major regulatory protein, is partially controlled by the differential activation of the sarA promoters. We previously partially purified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
97
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 94 publications
(102 citation statements)
references
References 32 publications
(37 reference statements)
4
97
1
Order By: Relevance
“…The reported structures of MarR family proteins show that the dimerization domain includes a-helices in the Nterminal and C-terminal regions of each monomer (Alekshun et al, 2001;De Silva et al, 2005;Hong et al, 2005;Lim et al, 2002;Liu et al, 2001;Wu et al, 2003). The protein-protein interaction is primarily mediated by a number of hydrophobic interactions, and is further stabilized by hydrogen bonds and salt-bridge pairs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The reported structures of MarR family proteins show that the dimerization domain includes a-helices in the Nterminal and C-terminal regions of each monomer (Alekshun et al, 2001;De Silva et al, 2005;Hong et al, 2005;Lim et al, 2002;Liu et al, 2001;Wu et al, 2003). The protein-protein interaction is primarily mediated by a number of hydrophobic interactions, and is further stabilized by hydrogen bonds and salt-bridge pairs.…”
Section: Discussionmentioning
confidence: 99%
“…Although the amino acid sequence similarity of this SlyA is relatively low, we demonstrated that the structure of this SlyA is very similar to the structures of the other MarR family proteins. The crystal structures of this protein family (which includes MarR, MexR, SarR, SlyA-Ef, AphA and OhrR) revealed that the protein forms a homodimer, with each subunit possessing a winged-helix DNA binding motif, which is required for DNA binding (Alekshun et al, 2001;De Silva et al, 2005;Hong et al, 2005;Lim et al, 2002;Liu et al, 2001;Wu et al, 2003). Furthermore, winged-helix proteins characteristically bind to DNA sequences containing a palindromic or pseudopalindromic structure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cognizant of our recent structural data showing that SarA is a dimeric winged helix protein (13), it is likely the binding site of SarA is greater than 17 bp in size and contains either a palindrome or an inverted repeat (based on our unpublished gel shift data with various sizes of the duplex DNA fragments and purified SarA protein), which is typical of most winged helix proteins with two winged helix motifs (e.g., OhrR, MecI, and BlaI), with each motif capable of binding to the major groove and minor groove of target DNA (11,12,21,22). Accordingly, the data presented here are consistent with a larger binding site for two winged helix motifs.…”
Section: Fig 4 (A)mentioning
confidence: 99%
“…Based on the reported structures, they proposed a ''shortening'' effect of DNA as a result of binding by the dimeric SarA protein, leading to gene activation (17). Independently, we reported the dimeric SarR structure to be a typical ''winged-helix DNAbinding protein'' in the absence DNA, with the helix-turn-helix (HTH) and the winged regions interacting with the major and minor grooves of target promoter DNA, respectively (18). We also proposed the two conserved acidic patches on the convex side of the SarR structure as possible functional motifs, whereas the concave surface, containing a tract of basic residues, is likely to be the DNA-binding side (18).…”
mentioning
confidence: 99%